Types and circumstances of marital union in the occurrence of physical intimate partner violence in Chiapas, Mexico, 2016 - Suárez Muñoz, Ana Laura (2022)
Violence against women in heterosexual couples is not only a very complex issue, but also a public health problem. The work contributes to the study not only in the type of conjugal union (cohabitation and marriage) but also taking into account the circumstances in which the union occurs, to explain both in indigenous and non-indigenous women their relationship with the magnitude and severity of the expressions of physical violence against women in Chiapas. The study was conducted through a quantitative approach taking as a basis data from the National Survey on the Dynamics of Household Relationships 2016 (ENDIREH); 2604 women aged 15 to 49 years, currently in union, indigenous and mestizo were included. The results show that free union is more frequent in indigenous women and that this type of union is significantly associated with a higher probability of occurrence of physical violence in its different expressions. Additionally, the circumstances in which the union is established provide evidence of differences in the frequency of physical violence in them, particularly when women are forced to join. The social disadvantage of women underlies the type and circumstances in which the union occurs, highlighting the participation or not of women in the decision to join and the normative aspects that govern unions in Chiapas, Mexico. Results are discussed in light of reproductive change and male involvement in the establishment of the union as elements underlying both cohabitation or marriage and intimate partner violence.